A qualitative exploration of how SENCos construct the term ‘acquired brain injury’ and associated support in UK primary schools: A Reflexive Thematic Analysis. - Herbert, Isobel Faye (2025)
Acquired brain injury (ABI) is a term used to describe a neurological injury that occurs to the brain after birth (Howe & Ball, 2013). In the UK, there are reports of up to 40,000 new cases of childhood ABI per year (Dunford et al., 2020). The impact of ABI on children has been linked to physical, cognitive, social and emotional needs (Wilkinson et al., 2017; Saly et al., 2023); highlighting the importance of providing appropriate and timely support in schools (Crowe et al., 2021). Current literature suggests that school professionals are often unaware of ABI and its impact (Ernst et al., 2017) and acknowledge their own gaps in knowledge relating to ABI (Chleboun et al., 2021), including frequent misconceptions (Bennett et al., 2022). However, there is limited research into how ABI and any associated support is constructed by school professionals, especially by Special Educational Needs Coordinators (SENCos), who often work closely with children with ABI (Linden et al., 2013). The current study aims to provide a novel insight into how SENCos in UK primary schools construct the term ‘acquired brain injury’ and any associated support for children with ABI. This study used semi-structured interviews and espoused itself to Reflexive Thematic Analysis (RTA) to gather and analyse data to explore SENCo constructions of ABI, based on a social constructionist positioning (Pilgrim, 2019). Six participants from mainstream UK primary schools participated in this study, who were all actively supporting children with special educational needs in a SENCo role for more than one academic year. Data was analysed using Braun & Clarke’s (2006 & 2021) six stages of RTA. A critically oriented analysis of the data interpreted that SENCos constructed ABI as complex in need, complex to support, easily misconceived, and requires a high level of support and significant growth in their role as a SENCo. Implications of these findings suggest that there is a need for increased awareness and knowledge of ABI through professional development and research, as well as multidisciplinary working. This research hopes to contribute to the limited literature on ABI in education from a SENCo’s perspective and highlights the need for systemic change to support inclusive and informed practice to support children and young people with ABI.